IMPROVING STUDENTS’ WRITING ACHIEVEMENT BY USING CLUSTERING TECHNIQUE OF THE EIGHT GRADE OF MTsN PARE - elisa, firdana (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 1 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Getting troubles to convey the English writing of the foreign learners’ in the classroom, the researcher experienced to do the research if clustering technique is able to improve students’ writing achievement of the Eight Grade of MTs N Pare. The research conducted Classroom Action Research (CAR) as the design. It was done in G class. There were 33 students which contained 14 male students and 19 female students. To know the result of students’ writing achievement was known by giving writing test, list of observation, list of questionnaire, and list of interview. However, the interview and the questionnaire were as the additional data to measure the result of students’ writing achievement. The result of the data counted the average and percentage of the writing achievement. The result of the research mentioned the improvement in every cycle. The average and the percentage shown the students’ writing achievement in cycle I was in 80,00 and 76,76%. The result of cycle II shown the improvement in average and the percentage in 82,50 and 87,87% students achieve the standard of success. The conclusion was that clustering technique is the technique which could improve students’ writing achievement.